2017
DOI: 10.1371/journal.pone.0174073
|View full text |Cite
|
Sign up to set email alerts
|

Plasma soluble L-selectin in medicated patients with schizophrenia and healthy controls

Abstract: Immune dysfunction has been implicated in the pathophysiology of schizophrenia. Leukocyte migration to the site of inflammation is a fundamental step of immune response which involves P-, E-, and L-selectins. Elevated selectin levels have been reported in un-medicated first-episode patients with schizophrenia but not in medicated patients with multi-episode schizophrenia. We measured fasting plasma soluble P-, E-, and L-selectin in 39 medicated patients with multi-episode schizophrenia and 19 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Moreover, although Kronig et al found decreased levels of sICAM in adults with SZ 29 , Stefanovic et al found that early-stage SZ patients had similar levels to that of HC, and they also observed increased levels of sICAM in older patients with a longer duration of illness 32 . Increased levels of sP-selectin were shown in adult patients with acute psychosis and AP exposure 30 , whereas Mohite et al reported no difference between HC and medicated, multi-episode patients 31 . As discussed above, these inconsistent findings could partly reflect variations in demographic characteristics between samples.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, although Kronig et al found decreased levels of sICAM in adults with SZ 29 , Stefanovic et al found that early-stage SZ patients had similar levels to that of HC, and they also observed increased levels of sICAM in older patients with a longer duration of illness 32 . Increased levels of sP-selectin were shown in adult patients with acute psychosis and AP exposure 30 , whereas Mohite et al reported no difference between HC and medicated, multi-episode patients 31 . As discussed above, these inconsistent findings could partly reflect variations in demographic characteristics between samples.…”
Section: Discussionmentioning
confidence: 95%
“…Reports on circulating levels of CAMs in adults with psychosis compared with healthy controls (HC) have been inconsistent, and both higher, lower, and similar levels of ICAM-1, VCAM-1, E-, L-, and P-selectin have been reported [27][28][29][30][31][32][33] . Because increased levels of several of these CAMs are associated with cardiometabolic risk factors and disease in the general population 34 , differences in demographics and comorbidity combined with staging differences could explain the inconsistency in reported levels 32 .…”
Section: Introductionmentioning
confidence: 99%
“…These CAMs may shed from the cell surface by different mechanisms and their soluble (s) form released into the circulation. As shown in Supplemental Table 1, many previous studies have evaluated circulating CAMs showing quite consistent upregulation of proteins such as sICAM-1 in SMI [18,[31][32][33][34][35][36][37], while inconsistent regulation is found for sVCAM-1 [31][32][33][34] and sP-SEL [38][39][40][41][42], possibly due to differences in sample material and controlling for different demographics. To our knowledge, systemic levels of sJAM-A and sN-CAD, have not been evaluated in SMI.…”
Section: Introductionmentioning
confidence: 99%
“…Blood zonulin was also elevated in the patients (SMD, 1.17; 95% CI, 0.04-2.30; p = 0.043) (80,81). We found no significant differences between all patients and controls for blood E- (82)(83)(84) or P-selectins (82,(84)(85)(86), intercellular adhesion molecule 1 (ICAM-1) 83, 86-93), vascular cell adhesion molecule 1 (VCAM-1) (83, 86,88,90,91,93), tissue inhibitor of matrix metalloproteinase1 (TIMP-1) (79, 94), TIMP-2 (79, 94), or plasminogen activator inhibitor-1 (PAI-1) (95-97). However, blood ).…”
Section: Junction Proteins and Modifiersmentioning
confidence: 62%